Comparative Analysis of the Financial Performance of Islamic Banking in Indonesia and Malaysia During the Covid-19 Pandemic - Safitri, Ika; Pramono, Sigid Eko; Zaenal, Muhammad Hasbi (International Journal of Economics (IJEC), 2024)
Financial performance as a measuring tool to determine the process of implementing financial resources owned by the company. The Covid-19 pandemic has had a significant impact on Islamic banking. where Malaysia and Indonesia are the leading countries in the development of the Sharia economy, of course they are affected by the Covid 19 Pandemic. The purpose of this study is to compare the financial performance of Islamic banking in Indonesia and Malaysia before and during the Covid 19 pandemic. The data analysis technique used is the independent sample t test. The variables being compared are NPF, FDR, ROA, ROE, CAR, and BOPO. The sample used in this study is in the form of sharia banking performance reports issued by financial services authorities from each country before and during the Covid-19 pandemic, namely from 2018-2021. The results show that in Islamic banking in Indonesia there are significant differences only in the CAR variable, while for NPF, FDR, ROA, ROE, and BOPO there are no significant differences between before and during COVID-19. Meanwhile, in Islamic banking in Malaysia, there are significant differences only in the BOPO variable, while for NPF, FDR, ROA, ROE, and CAR there are no significant differences between before and during COVID-19. And for the comparison of performance between Indonesian and Malaysian Islamic Banking, there is a significant difference in the performance of the two countries except for the NPF variable, there is no significant difference between the NPF of Indonesian Islamic Banks and Malaysian Islamic Banks during the 2018-2021 period